Determination of the influence of the economic cycle stages on the innovative potential of small entrepreneurship - Lykholat, S.; Krykavskyi, Y.; Lozynskiy, V.; Shynkarenko, N. (Видавництво Львівської політехніки, 2021)
The small business sector is studied. It is hypothesized that the small business sector has a significant innovative potential, the possibilities of which depend on the economic cycle of market conjuncture. It has been hypothesized that innovation investment in the small business sector depends significantly on economic cycles, and that the structure / directions of innovation investment are determined by the global market conjuncture. This is done in order to interpret the systemic / unsystematic development of small business in the context of public policy on the basis of appropriate calculations and the obtained results, as well as provides an understanding of the possibilities of realizing the innovative potential of small business. The peculiarity of this study is its complementarity “innovative potential of small business – technology transfer – economic cycles”. It has been established that investment in innovation and technology transfer in the small business sector depend on market conjuncture and stages of the economic cycle that occur in a certain period (growth or recession). The identification of economic cycles allowed to form the directions of state regulation and reveal the possible risks associated with finding the innovative potential of small business. The conducted research creates a basis for the implementation of the cluster policy program; contributes to the formation of appropriate tools for creating clusters; reveals favorable periods of labor involvement in the realization of innovation potential; helps to identify the periods of economic cycles in which it is appropriate to invest in their own self-education and modern technology. This approach will help increase the level of balance of the small business system on an innovative basis.
Keywords: innovation potential; small business; transfer of technological solutions; investment of innovations; economic cycles; information systems; E32; 330.33.012